Relationship between Burnout, Cardiovascular Risk Factors, and Inflammatory Markers: A Protocol for Scoping Review - Oladimeji Adebayo; Misheck J. Nkhata; Kehinde K. Kanmodi; Taiwo Alatishe; Eyinade Egbedina; Temitope Ojo; Samson Ojedokun; John Oladapo; Abiodun Moshood Adeoye; Lawrence A. Nnyanzi (Journal of Molecular Pathology, 2023)
Background: Burnout is increasingly being recognized as a contributory factor to the erosion of a positive psychological state. Studies have examined the relationship between burnout and various inflammatory markers such as IL-1, IL-6, and TNF-alpha. Burnout is also associated with increased systemic inflammation along a continuum of symptom severity. This protocol is for a scoping review looking at the link between burnout, inflammatory markers, and cardiovascular risks or diseases. Methods: This study will be based on the preferred reporting items for systematic reviews and meta-analyses guidelines/checklists and the report of the review will be based on the same guideline. The study seeks to address the following principal questions. (i) What are the relevant inflammatory biomarkers that mediate cardiovascular risk factors in burnout? (ii) How do inflammatory biomarkers mediate cardiovascular risk factors in burnout? The outputs obtained from the literature search will be deduplicated using the Rayyan software. Results: We would create table summaries of findings to inform a narrative synthesis of the evidence from the papers included. Conclusion: The review article would help to concisely synthesize the available evidence on the relationship between burnout, inflammatory markers, and cardiovascular diseases.